Gender education of adolescent boys in general educational organizations - Valentina V. Maryuhina, Sayzana A. Araptan, Natalya Sh. Damba,; Mayya D. Dorzhu, Ailan S. Kombu, Argaana B. Oorgak, (Opción, 2019)
The proposed article reveals the main scientific views on the problems of gender education at the level of general education institutions, in particular, at the regional level in the Republic of Tuva. The result of the experiment was the identification of three typological groups of students with different indicators of the level of masculine and feminine traits. As a conclusion, an educational factor, formed on the basis of gender approach, revealed pedagogical conditions and implemented in the model, can be an effective factor in taking into account individuality, developing potential opportunities and improving the quality of educational achievements of students